Pemanfaatan Air Buangan Ac Untuk Tanaman Hias Berbasis Internet Of Things - Eky Arjayanto Nurhasana; Hermansyah Hermansyah; Lely Aylia; kasim kasim (Jurnal Teknologi Elekterika, 2019)
In relation to utilizing AC waste water and the use of water in watering plantsespecially ornamental plants and provide awareness for efforts to save water. By usingapplication of Internet of Things (IoT) based electronic circuit which is one of the programsdeveloped to facilitate the process of watering and fertilizing plants automatically. One ofthe way you can do this is by using IoT devices as a control device.This product is expected to be a product that can be sold to the market at an affordable price. andhas a function that is environmentally friendly and can be used by all people in the future. Activitiesmaking this product starts with the initial stage of observing the room using AC and makingdesign model, after getting the right room, then is to prepare the device to beused to make products both electronic and non-electronic devices and finally prepare toolswhich will be used for installation and configuration of the tool. After the product is finished, the next is testingproduct. The final stage includes functional checks to determine whether the tool is functioning properly based onsystem design that has been designed.